2021
DOI: 10.1051/ro/2021166
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturer’s cooperation strategy of closed-loop supply chain considering corporate social responsibility

Abstract: Corporate social responsibility (CSR) has become a popular and important strategy for corporate operation and sustainable development. Meanwhile, many social or environmental incidents that occur in one enterprise could bring huge risk or disruption for the entire supply chain. This study discusses the manufacturer’s cooperation strategy of closed-loop supply chain (CLSC) composed of a dominant manufacturer with CSR behavior consciousness, a retailer with CSR investment, and a third-party recycler. In the CSR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…Part (i) of Corollary 1 shows that, with manufacturer CSR, whether there is manufacturer encroachment or not, the higher the CSR level, the lower wholesale price will be set at. Previous studies have obtained similar conclusions, for example, Yan et al (2021). The reason might be that as the manufacturer becomes more aware of its CSR behavior, it will take the initiative to reduce wholesale prices in the retail channel to better benefit stakeholder, thus maximizing social welfare (Corollary 3 also suggests that manufacturer's social welfare maximization goal is positively related to its awareness of CSR behavior).…”
Section: Equilibrium Solutionssupporting
confidence: 73%
See 1 more Smart Citation
“…Part (i) of Corollary 1 shows that, with manufacturer CSR, whether there is manufacturer encroachment or not, the higher the CSR level, the lower wholesale price will be set at. Previous studies have obtained similar conclusions, for example, Yan et al (2021). The reason might be that as the manufacturer becomes more aware of its CSR behavior, it will take the initiative to reduce wholesale prices in the retail channel to better benefit stakeholder, thus maximizing social welfare (Corollary 3 also suggests that manufacturer's social welfare maximization goal is positively related to its awareness of CSR behavior).…”
Section: Equilibrium Solutionssupporting
confidence: 73%
“…For an earlier review of CSR conception, please refer to Frederick (1987). Most studies focus on the supply chain members' CSR strategy, that is, CSR concern (He et al, 2019; Liu & Xiao, 2019; Modak et al, 2014, 2019; Panda et al, 2015, 2017; Wang et al, 2021; Wang & Li, 2021; Ying et al, 2023), CSR investment (Arya & Mittendorf, 2015; Liu et al, 2019, 2021; Ma et al, 2017; Modak et al, 2019; Ni & Li, 2012; Wu et al, 2017, 2020; Yan et al, 2023), CSR sharing (Hsueh & Chang, 2008; Ni et al, 2010; Syed Asif Raza, 2018), and CSR affect (Nie et al, 2019; Yan et al, 2021). Our work uses consumer surplus to measure the CSR of manufacturer and retailer, corelated with the first issue.…”
Section: Related Literaturementioning
confidence: 99%
“…Research shows that the recovery rate is higher under recycler leadership than centralized decision-making and manufacturer leadership. Yan et al [31] explored the manufacturer's cooperation strategy of CLSC composed of a dominant manufacturer with CSR behaviour consciousness, a retailer with CSR investment, and a third-party recycler.…”
Section: Channel Power Structurementioning
confidence: 99%
“…They found that a more significant market share and higher system profit can be obtained only through CSR cooperation among member enterprises. Yan et al (2021) discussed a closed-loop supply chain cooperation strategy composed of manufacturers with social responsibility consciousness, retailers with CSR investment and recyclers. They found that CSR consciousness can motivate each other and improve the overall performance of the supply chain.…”
Section: Literature Reviewmentioning
confidence: 99%